Americanization in the Rainbow Nation: Remote Acculturation and Psychological Well-Being of South African Emerging Adults. (April 2016) - Ferguson, Gail M.; Adams, Byron G.
This article expands remote acculturation research by exploring the presence, vehicles, and well-being implications of Americanization in a racially diverse group of post-Apartheid emerging adults in Johannesburg, South Africa ( N = 370, M age = 19.8 years: 63% Black, 21% White, 11% Indian, and 5% Coloured). Cluster analyses revealed three Americanized South African clusters constituting 71% of the sample (i.e., African-Americanized, European-Americanized, and Multicultural-Americanized), and one culturally traditional cluster (29%). Receiving U.S. goods and consuming U.S. fast food were the primary vehicles of Americanization. European-Americanized youth had higher life satisfaction than Traditionals and lower psychological distress than African-Americanized youth, after controlling for race. However, remote acculturation was not linked to family values or family conflict. Taken together with prior research, the bicultural and multicultural patterns of remote acculturation profiles appear to be culture universals, although the form (e.g., remote culture targeted) and well-being implications of remote acculturation (i.e., psychological and family) appear to be culture-specific.